TINJAUAN HAK LINTAS DAMAI DI LAUT TERITORIAL DALAM PERSPEKTIF HUKUM NASIONAL DAN INTERNASIONAL - Melinda Gultom; Suhaidi Suhaidi; Arif Arif (Journal of USU International Law, 2017)
ABSTRACT OVERVIEW OF THE PEACE RIGHTS IN THE TERRITORIAL SEA IN NATIONAL AND INTERNATIONAL LAW PERSPECTIVES Melinda Gultom* Suhaidi** Arif*** Indonesia is the largest archipelago country in the world. As an archipelagic country with vast sea and long coastlines, maritime and maritime sectors are becoming very strategic for Indonesia. In this regard, Indonesian waters must be protected judicially from the threat of lawlessness as a result of non-compliance with applicable national and international laws. This research formulates issues concerning the regulation of peace rights under national law, the arrangement of the right of peace in international maritime law and the enforcement of foreign ships in Indonesian territorial sea the relevance of the right of peace. The method used in this study is the normative juridical method with data collection techniques in the form of document studies and legislation. The result of the research that since Djuanda Declaration, the Government of Indonesia continue to strive for the concept of insight of the archipelago to the countries in the world in international forums both bilaterally, trilateral and multilateral, the result of diplomacy is the acceptance of the Islands State in UNCLOS 1982. Then in the right of peace transnational state must respect the right of peaceful passage for foreign vessels to pass through its archipelagic waters in accordance with the provisions and regulations applicable in UNCLOS 1982 and law enforcement for foreign vessels in Indonesian waters has been regulated in legislation in the form of Conventions, Declarations and Laws nationally, but the facts on the ground proved a violation committed by foreign ships crossing the Indonesian territorial sea. Keywords: Lintas Damai, Teriorial Sea, National and International Law